Effect of Fruit Powders as Natural Alternatives to Sodium Nitrite on Lipid Oxidation in Clean-Label Salami - Adriana-Ioana Moraru Manea; Ileana Cocan; Delia-Gabriela Dumbrava; Mariana-Atena Poiana (Foods)
Public concerns about the health risks of synthetic antioxidants have prompted the meat industry to look for natural alternatives rich in phenols with strong antioxidant properties. This study investigates the use of blackcurrant (BCP), lingonberry (LP), and sour cherry (SCP) powders as natural substitutes for synthetic nitrites in reformulating two clean-label salami types, smoked and cooked and smoked and scalded, with a focus on their effects on oxidative stability during processing and refrigerated storage (4 °C). Nitrite-free formulations were prepared with each fruit powder at three inclusion levels to provide total phenolic contents of 90, 200, and 300 mg gallic acid equivalents (GAE)/kg of processed meat. A nitrite-containing control (90 mg/kg) and an additive-free control were included for comparison. The phytochemical profiles of powders were characterized by total phenolic, flavonoid, monomeric anthocyanin contents, and L-ascorbic acid levels. Antioxidant activity was assessed via 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging and ferric reducing antioxidant power (FRAP) assays. Salami samples were analyzed for proximate composition, and lipid oxidation was monitored at 0, 15, and 30 days of storage using peroxide value, inhibition of oxidation, p-anisidine value, TOTOX, and thiobarbituric acid value. Fruit powders demonstrated dose- and type-dependent inhibition of primary and secondary lipid oxidation, enhancing oxidative stability during processing and storage. After 30 days of storage, oxidation markers in fruit-enriched salami remained below recommended thresholds, confirming effective control of lipid oxidation. The inhibitory potential followed the order BCP > LP > SCP, consistent with antioxidant profiles as reflected by DPPH and FRAP values. BCP at 300 mg GAE/kg showed a stronger lipid oxidation inhibition than sodium nitrite. Promising improvements in lipid oxidation resistance were also observed with LP at 300 mg GAE/kg and BCP at 200 mg GAE/kg. These findings highlight the potential of fruit-derived antioxidants to support the development of more sustainable, value-added meat products without compromising quality.